Article 565-A of the CPC: constitutional jurisprudential study of the maintenance creditor’s right of access to justice - Palacios Baltazar, Nataly M. (2023)
Maintenance proceedings and their versatilities (exoneration, reduction, proration and variation) are one of the litigious problems of high demand in the judicial districts of our country, so much so that there are currently specialized courts of the peace that resolve litigation only in this area. In addition, the judicial processes referred to constitute one of the most sensitive matters within family law, as they are used to provide effective jurisdictional protection to children, adolescents and other vulnerable populations (the disabled, the elderly and others). In this context, we wanted to study article 565-A of the Code of Civil Procedure, which to date has been generating contradictory jurisdictional pronouncements in its application; thus, for example, it is observed that some jurisdictional bodies apply literally the requirement demanded by the article in question and declare the claim inadmissible, which is even confirmed in the second instance; while in other jurisdictional bodies it is not applied to the specific case -via diffuse control- and the proceedings are elevated to the Supreme Court of Justice of the Republic for the respective consultation. In this context, we seek to conduct a constitutional jurisprudential analysis of the rights involved, that is, on the side of the obligor and on the side of the provider, so that by using the proportionality test we can determine whether the right of access to justice of the maintenance creditor is violated by the application of the aforementioned article. At the end of the investigation, it has been concluded that article 565-A of the CPC does not violate the right of access to justice of the maintenance creditor; on the contrary, it optimizes the right to the effectiveness of judicial decisions of child and adolescent maintenance creditors.